Low bone mineral density as predictor factor for loss of teeth - Irene Edith Rieuwpassa; Nurul Fitri; Wahyu Aji Ramadhan (Makassar Dental Journal PDGI Makassar, 2018)
Low bone mineral density is a clinical condition in patients with osteoporosis. Osteoporosis is a degenerative metabolic disease characterized by reduced bone mass and bone microarchitecture; so it risks for fracture. The prevalence of osteoporosis increases with the increasing life expectancy and preponderance of females. This paper aims to determine the influence of decreased bone mineral density of the missing teeth terhadap tooth loss which contributes to early prevention of tooth loss in people with osteoporosis and osteopenic. The method used to assess bone mineral density reduction is by using dual energy x-ray absorptiometry (DXA) while the loss of teeth can be seen by clinical and radiological examination of the oral cavity with a panoramic technique. Tooth loss is a condition that must be experienced by the end of dental periodontal disease which is present in a progressive inflammatory process, periodontal attachment loss and decreased alveolar bone supporting the teeth. The high rate of decline in bone mineral density can lead to faster loss of teeth because of hormone deficiency in elderly women or men. This condition affects the activity of osteoclast and osteoblast, causing abnormalities bone turnover on the whole body including the alveolar bone and showed relationship between decreased of bone mineral density with tooth loss in the elderly. The conclusion is the presence of hormone deficiency in the process of interaction osteoblast and osteoclast leads to decreased bone mineral density in elderly include in jaw bone and it causes rapid tooth loss.